Analysis of influencing factors of rupture phenomenon of liquid film on the wall of corrugated plate dryer. (November 2020) - Wang, Bo; Chen, Bowen; Wang, Gongqing; Ke, Bingzheng; Wen, Jiming; Lu, Chuan; Tian, Ruifeng; Deng, Jian
Highlights: Method to delay rupture of the liquid film on corrugated plate wall is given. Increasing radius of curvature can suppress the occurrence of liquid film rupture. PLIF method is used to measure liquid film thickness on the wall. Effect of corrugated plate spacing on liquid film rupture is not obvious. Abstract: Corrugated plate dryer is an important steam-water separation equipment in secondary loop of nuclear power plants. Rupture of liquid film on corrugated plate wall will inevitably affect steam-water separation efficiency. In this paper, based on the liquid film rupture model that we derived earlier, influencing factors of liquid film rupture are given. Effects of liquid film thickness, linear distance between two corrugated plate walls, radius of curvature at the position of inflection angle of corrugated plate on critical airflow speed were experimentally analyzed. Results show that the larger the radius of curvature, the higher the critical airflow speed. When inflection angle increases to a certain value, the increase in the radius of curvature has little effect on film rupture. As the linear distance between corrugated plate walls increases, critical airflow speed will increase. However, effect of linear distance between corrugated plate walls on liquid film rupture is not obvious.